Treatment of pharmaceutical wastewater containing tylosin in an anaerobic-anaerobic reactor system - Chelliapan, Shreeshivadasan (IWA Publishing, 2010)
Effluents from manufacturing operations in the pharmaceutical industry, such as antibiotic formulation, usually contain recalcitrant compounds. An approach towards appropriate technology for the treatment of pharmaceutical wastewaters has become imperative due to strict water quality legislation for environmental protection. In the present study, an Up-Flow Anaerobic Stage Reactor (UASR) and a Porous Membrane Activated Sludge Reactor (PMASR), operating in series, were used to treat pharmaceutical wastewater containing the macrolide antibiotic Tylosin. The performance of UASR treating real pharmaceutical wastewater at various organic loading rates (OLR) (0.43 to 3.73 kg COD.m–3.d–1) was investigated. Effluent from the UASR was passed directly into a PMASR system in a continuous process. At a reactor OLR of 1.86 kg COD.m–3.d–1 (hydraulic retention time (HRT), 4 d), the soluble COD reduction was around 70 - 75% (average specific degradation rate (SDR), 1.29 kg COD.m–3.d–1 ) an average of 95% Tylosin reduction was achieved in the UASR. During this period, the soluble COD removal efficiency of the PMASR was 63–69% (average SDR, 0.37 kg COD.m–3.d–1). The combined UASR – PMASR treatment system was slightly more effective with 87–90% COD and average 97% Tylosin removal. The results indicate successful treatment of the pharmaceutical wastewater, and confirm Tylosin degradation, providing further evidence that Tylosin can be degraded efficiently in anaerobic-aerobic environments.